TOWARD INDONESIA’S AGROINDUSTRIES COMPETITIVENESS: THE CASE OF BIOETHANOL DEVELOPMENT FROM SUGARCANE BASED INDUSTRIES - Indahsari, Gita K.; Wibowo, Rudi (European Scientific Journal, ESJ, 2013)
World oil price has been fluctuating throughout the years, however the trend continues to increase. Due to limited sources of oil production and high demand for world oil, it is predicted in ten years from 2010, world oil price could even reach as high as triple digit per barrel. Countries around the world had continuously tried to produce alternative energy, including Indonesia. The Indonesian government had tried to develop this industry, with roadmaps and targets for alternative energy production, reduce dependency on fossil fuel until the next ten years to come. The objective of this paper is to study the bioethanol industry developed by PTPN X. The bioethanol industry is still at its early stage in Indonesia. Problems to develop this industry includes finding the most potential raw materials used, availability of the industry, stage of competition with other uses of the raw materials until end product and marketing. From many potential raw materials, sugarcane is one of the most potential source of bioethanol. PTPN X case study shows how bioethanol can be competitive if there are supporting factors such resources, technology and company size. The comparative advantage of PTPN X is the ability of PTPN X to incorporate problems from upstream to downstream of the supply chain of bioethanol. Methods such as the EPC, ANP, Diamond Porter Model and case study of PTPN X are used to demonstrate the potential of sugarcane as an alternative energy and the ability of PTPN X to develop a competitive agroindustry.